Effects of hyaluronic acid on bleeding following third molar extraction - Gokhan GOCMEN; Sertac AKTOP; Burcin TÜZÜNER; Bahar GOKER; Aysen YARAT
Abstract Objective To explore the effects of hyaluronic acid (HA) on bleeding and associated outcomes after third molar extraction. Methods Forty patients who had undergone molar extraction were randomly divided into two groups; 0.8% (w/v) HA was applied to the HA group (n=20) whereas a control group (n=20) was not treated. Salivary and gingival tissue factor (TF) levels, bleeding time, maximum interincisal opening (MIO), pain scored on a visual analog scale (VAS), and the swelling extent were compared between the two groups. Results HA did not significantly affect gingival TF levels. Salivary TF levels increased significantly 1 week after HA application but not in the control group. Neither the VAS pain level nor MIO differed significantly between the two groups. The swelling extent on day 3 and the bleeding time were greater in the HA group than in the control group. Conclusions Local injection of HA at 0.8% prolonged the bleeding time, and increased hemorrhage and swelling in the early postoperative period after third molar extractions.